ECIES for Group Key Establishment in WSN for Secure Multicast Communication (International Journal of Engineering and Computer Science, 2017)
A wireless sensor network (WSN) as the name suggest is a wireless network with spatially distributed autonomous devices makinguse of sensors for monitoring physical or environmental conditions. WSNs find applications in areas like healthcare, home automation,traffic control etc. WSN with characteristics of self-organization, multi-hop, dynamic topology and limited energy resources, make itextremely difficult to prolong the lifetime of the network. To prolong the life time of WSN with limited energy resources, Multicast canbetter meet the requirements of network resources. It has an active significance for WSN to increase its performance in the near future. InWireless sensor networks sensor nodes are grouped together by forming multicast groups. The communication among the nodes is done bybroadcasting and multicasting efficient message deliveries among resource-constrained sensor nodes. Two group key protocols aredeveloped for secure multicast communications among the resource-constrained devices. The proposed approach compares the performanceof two protocols with ten nodes in each group. We analyze the proposed solution to evaluate the performance using Network Simulator-2(NS-2) under different network parameters with a number of destination nodes.